Mulla Sadra’s Doctrine of the Primacy of Existence (Asalat Al-Wujud) - Moris, Megawati (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Mulla Sadra’s Doctrine of the Primacy of Existence (Asalat Al-Wujud)